Translation of Film Titles Based on Intercultural Communication - Qin, Jing (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
To illustrate cultural differences between China and the western world in translating film titles. Film industry plays a vital role in cultural communications, especially in the trend of globalization, which attaches a greater importance to film title translation than ever before. Some of theories concerning cultural differences will be discussed, including Hall’s high-context and Low-context orientations and Hofstede’s value dimensions. The study finds that with the help of these theories, certain translation methods can be utilized by translators in order to do a better job when translating titles of imported films.